Gender Disparities in Socio-economic and Demographic Characteristics among Older People - Dahal, Ramchandra (Siddhajyoti Interdisciplinary Journal, 2025)
This study aims to understand the demographic and socio-economic characteristics of individuals aged 60 and above in Kamalamai Municipality, Sindhuli, selected for its diverse socio-economic background of this research. Using a descriptive research design with a two-stage stratified sampling method, 371 households with elderly members were surveyed. Data collection technique involved information on demographic, health, and socio-economic variables, analyzed by cross tables. The findings indicate significant demographic insights, including age distribution and marital status, highlighting that 33.7 percent of respondents were aged 60-64, with a higher proportion of females. Socio-economic characteristics showed varied literacy rates, education levels, and media usage, with 69 percent of respondents being literate. Economic data revealed asset ownership, land possession, and debt status, with 69.3 percent having assets and 38.5 percent possessing debt/loans. Social security awareness was high, but pension receipt was low. Overall, the study provided valuable insights into the elderly population’s demographics and socio-economic conditions, emphasizing the need for tailored policies and support systems to enhance their quality of life. The comprehensive analysis offers a better understanding of their living conditions and needs in Kamalamai Municipality Ward No. 4, Sindhuli.